النشاطات واأللعاب اللغوية لتعليم املفردات - Rahmawati, Rahmawati (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2015)
The paper is intended to highlight the use of language games as interactiveactivities in the classroom. The use of games in the classroom may help studentsto avoid monotonous classroom, and teachers can improvise their competence indesigning language games that are useful and meaningful, and students havethe desire to participate and contribute. Language games are used for learners tocollaborate among others and to achieve educational objectives. Games becomemeans to enrich the training of language skills, especially the material taught. Ofcourse it could be successful if it corresponds to the number, age and languagelevel of the students as well as considering a psychological condition, and theavailability of the game apparatus.